Immunohistochemical Analysis of Asprosin and Meteorin-Like Peptide in Melanocytic Nevus and Malignant Melanoma - Demir, Betul; Cicek, Demet; Yuksel, Esma Inan; Kocaman, Nevin; Calik, Ilknur; Karstarli Bakay, Ozge Sevil; Gural, Yunus (Yuzuncu Yil Universitesi Tip Fakultesi, 2025)
Introduction: Asprosin (ASP) plays many important roles in the central nervous system, peripheral tissues, and organs, such as appetite, glucose metabolism, insulin resistance, and cell apoptosis. Many experimental and clinical studies have examined the effects of meteorin-like peptide (METRNL) on inflammation. This study aimed to examine the immunohistochemical analysis of ASP and METRNL in healthy skin, melanocytic nevus, and malignant melanoma and to investigate their possible role in melanocyte proliferation an d whether ASP and METRNL are potential biomarkers for melanocytic tumor development. Materials and Methods: A total of 36 skin samples, including 12 benign nevi, 8 dysplastic nevi, 6 malignant melanoma, and 10 healthy skin around lesions removed from breast tissue that was not exposed to the sun as a control group were included in this study. The skin samples were stained immunohistochemically using the avidin-biotin-peroxidase complex method. Results: ASP and METRNL expressions were detected in the epidermis and hair follicles of healthy s kin. No significant difference was detected in ASP and METRNL histoscores in tumor tissues of benign nevus, dysplastic nevus, and malignant melanoma (p>0.05). Conclusion: Current findings suggest that ASP and METRNL may be associated with cell-to-cell interactions between keratinocytes, melanocytes, and inflammatory cells and may be effective in melanocyte functions. Future studies will clarify whether ASP and METRNL are potential biomarkers for melanocytic tumor development. © 2025, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Asprosin; malignant melanoma; melanocytic nevi; meteorin-like peptide